The emergence and development of complex predicates in early child Hebrew. Issue 4 (August 2021) - Lustigman, Lyle
The present study examines the development of the earliest type of complex predicates to emerge in child Hebrew – extended predicate constructions. These constructions take the form of a modal/aspectual operator followed by an infinitival verb form (e.g., roce lesaxek 'want to.play'), and since they serve various discursive functions (e.g., intent, desire, request), their use marks a significant development in toddlers' cognitive, linguistic, and conversational abilities. Focus here is on the three most common modal operators used in extended predicates in early child Hebrew: roce 'want', yaxol 'can', and carix 'need/have.to'. Analyses cover all uses of these three predicates by both children and adults, in longitudinal weekly-recorded speech samples from three Hebrew-acquiring children, starting with the earliest verb forms produced by each child and lasting for a period of over a year (age range: 1;3–2;5). Findings show the following developmental trends: (a) roce 'want' emerges the earliest and continues to be the most frequent of the three predicates throughout the year; (b) children favor using roce, yaxol, and carix as main predicates before they start integrating them in extended-predicate contexts; (c) early adult uses of extended predicates in child-directed speech are almost exclusively in the form of Yes/No verification questions (e.g., ata roce laševet? 'you want to.sit?'); and (d) as children gradually use more extended predicates, adults gradually use fewer Yes/No verification questions, and more prompts that elicit information from the children (e.g., ma ata roce la'asot? 'what (do) you want to.do?') while also expanding more on the children's productions. These concurrent trends show that such complex predicates develop in a piecemeal fashion, promoted by both the gradually evolving relations between children's linguistic productions and their discursive functions, and the supportive contexts provided by their adult interlocutors.